Effect of reliance on Xpert MTB/RIF on time to treatment and multidrug-resistant tuberculosis treatment outcomes in Tanzania: a retrospective cohort study. Issue 6 (26th February 2019) - Mollel, Edson; Lekule, Isack; Lynen, Lutgarde; Decroo, Tom
Abstract: Background: During 2009–2013, Xpert MTB/RIF testing was decentralized in Tanzania. Standardized treatment of multidrug-resistant/rifampicin-resistant tuberculosis (MDR/RR-TB) was centralized at the Kibong'oto Infectious Diseases Hospital. Initially, Xpert MTB/RIF results were confirmed and complemented with phenotypic drug susceptibility testing before MDR-TB treatment was started. Since 2013, the decision to start MDR-TB treatment in patients with RR-TB relied on Xpert MTB/RIF results. Methods: A retrospective cohort study of predictors of unsuccessful treatment outcomes (including death, lost to follow-up and treatment failure) was carried out. Results: During the study period, 201 patients started MDR-TB treatment. The number of patients starting MDR-TB treatment increased over time. Out of 201 patients, 48 (23.9%) had an unsuccessful treatment outcome. The median time between sample collection and MDR-TB treatment initiation was reduced from 155 d (IQR 40–228) in the 2009–2012 period to 26 d (IQR 13–64) in 2013. Patients who started MDR-TB treatment in 2013 were more likely (adjusted OR 2.3; 95% CI 1.1–4.7; p=0.02) to have an unsuccessful treatment outcome. Conclusions: Xpert MTB/RIF testing increased enrolment on MDR-TB treatment. Reliance on Xpert MTB/RIF results to start MDR-TB treatment reduced time to treatment. However, treatment outcomes did not improve.